2013
DOI: 10.1002/mame.201200449
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Thermomechanical Degradation of LDPE/Modified Clay Nanocomposites

Abstract: The special features of polymer nanocomposites are continually gaining interest both in academia and in industry. The latter is especially experiencing an increase in interest towards this class of polymer composites, and this is leading to the first concerns about their reprocessing and reciclability.Here, a systematic study on the behavior of LDPE/Cloisite 15A systems upon reprocessing in a single-screw extruder is described, focusing on rheological, mechanical, and morphological properties changes. The inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
5
24
0
Order By: Relevance
“…However, this behavior, and in particular the retained ductility of the nanocomposite sample in comparison to the matrix, seems to suggest that a fair dispersion degree of the particles was obtained. These results are in agreement with those of similar systems 8,9 : the nanoparticles help in increasing the elastic modulus and keeping an almost constant tensile strength, while a slight, reduction in the elongation at break occurs; this is typically observed when an intercalated structure is obtained, therefore, also on the basis of the above discussed evidences from XRD analysis, it can be concluded that a moderate intercalation has actually occurred in the prepared nanocomposites.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, this behavior, and in particular the retained ductility of the nanocomposite sample in comparison to the matrix, seems to suggest that a fair dispersion degree of the particles was obtained. These results are in agreement with those of similar systems 8,9 : the nanoparticles help in increasing the elastic modulus and keeping an almost constant tensile strength, while a slight, reduction in the elongation at break occurs; this is typically observed when an intercalated structure is obtained, therefore, also on the basis of the above discussed evidences from XRD analysis, it can be concluded that a moderate intercalation has actually occurred in the prepared nanocomposites.…”
Section: Resultssupporting
confidence: 91%
“…Actually, the very high surface contact area between the two phases allows an easy and efficient transmission of the stress between the two phases, thus enhancing the beneficial effect of the filler. Mechanical properties, [1][2][3][4][5][6][7][8][9] rheological behavior, [10][11][12][13][14][15][16][17][18][19] and permeability [20][21][22][23][24][25] are dramatically influenced even by very small amounts of nanofiller.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, at higher shear rates (the typical processing range of injection molding operations) the nanocomposites show slightly lower values of viscosity. Therefore, the nanosized fillers display a trend in opposition to that which is typically observed in microcomposites, in agreement with the findings in similar systems [ 13 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 91%
“…Several papers also investigated the possibility to recycle biodegradable polymers in order to reduce the environmental impact related to the life cycle of biodegradable polymer-based items [5][6][7][8][9][10][11]. Among the different recycling routes, mechanical reprocessing represent an easy and low cost method [12,13]. Among biodegradable polymers, poly(lactic acid) (PLA) gained much attention thanks to its interesting properties including good processability, mechanical properties and performance, making it a good candidate for replacing commodities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymer nanocomposites, have received a great interest because they exhibit good mechanical, thermal and barrier properties [14,15]. Due to the growing market of nanocomposites, the scientific literature has currently studied the effect of reprocessing of the nanocomposites based on conventional polymers [13,[16][17][18][19]. Moreover, several studies investigated the effect of the reprocessing on the properties of neat biodegradable polymers, such as PLA [5,6,8,20].…”
Section: Introductionmentioning
confidence: 99%